Knockdown of STAT3 expression by RNAi induces apoptosis in astrocytoma cells. - Konnikova, Liza.; Kotecki, Maciej.; Kruger, Mathew M.; Cochran, Brent H. (2016)
Background: Astrocytomas are the most common type of primary central nervous system tumors. They are frequently associated with genetic mutations that deregulate cell cycle and render these tumors resistant to apoptosis. STAT3, signal transducer and activator of transcription 3, participates in several human cancers by inducing cell proliferation and inhibiting apoptosis and is frequently activated in astrocytomas.; Springer Open.